Linking knowledge with action when engagement is out of reach: three contextual features of effective public health communication. Issue 10 (30th August 2021) - Emmelhainz, Roger; Zarychta, Alan; Grillos, Tara; Andersson, Krister
Abstract: Scholars and practitioners often promote direct engagement between policymakers, health workers and researchers as a strategy for overcoming barriers to utilizing scientific knowledge in health policy. However, in many settings public health officials rarely have opportunities to interact with researchers, which is a problem further exacerbated by the coronavirus disease 2019 pandemic. One prominent theory argues that policy actors will trust and utilize research findings when they perceive them to be salient, credible and legitimate. We draw on this theory to examine the conditions facilitating greater uptake of new knowledge among health officials when engagement is out of reach and they are instead exposed to new ideas through written mass communication. Using data from a survey experiment with about 260 health workers and administrators in Honduras, we find that messages from a technocratic sender based on statistical evidence improved perceptions of salience, credibility and legitimacy (SCL). Additionally, perceptions of SCL are three contextual features that operate as joint mediators between knowledge and action, and several individual characteristics also influence whether officials trust research findings enough to apply them when formulating and implementing health policies. This research can help inform the design of context-sensitive knowledge translation and exchange strategies to advance the goals of evidence-based public health, particularly in settings where direct engagement is difficult to achieve.